Undisciplining the study of religion: critical posthumanities and more-than-human ways of knowing - von Stuckrad, Kocku (Religion, 2023)
Recent discussions about other-than-human agency and relationality across species and lifeforms are closely tied to theoretical reconsiderations within, and beyond, the humanities. Scholars in the study of religion have only reluctantly picked up these considerations. Theoretical work that includes nonhuman animals in conceptualisations of religion often still operates in binary structures of nature/culture and body/mind. The author reviews recent naturalistic approaches to concepts of religion and combines them with discussions in critical animal studies and biosemiotics, as well as with Karen Barad’s theory of agential realism, which forms the basis of a robust analytical frame of nonhuman agency. The author proposes a critical posthumanities study of religion, transforming and ‘undisciplining’ the humanities into a form of scholarly engagement that creates a transversal field of knowledge, consisting of human and other-than-human intra-actions—a study of religion that intentionally leaves behind the regimes of mastery and exploitation that are still operative today.